Sharks and their relatives: can their past help predict their future? - Hasenei, Aaron; Donelson, Jennifer M.; Ravasi, Timothy; Rummer, Jodie L. (Frontiers in Marine Science, 2023)
Elasmobranchs (i.e., sharks, skates, and rays) have survived five mass extinction events and changed relatively little throughout their 450-million-year evolutionary history. Therefore, elasmobranchs may provide critical evolutionary perspectives on how species and populations can elicit phenotypic plasticity and adaptation responses to climate change. Unfortunately, despite their roles as critical apex- and meso-predators, most elasmobranch species are considered to be highly vulnerable to the impacts of fisheries exploitation and climate change, which is compounded by their K-selected life history strategies. Furthermore, the future of elasmobranchs is uncertain at best in the face of anthropogenic climate change because there have only been a handful of studies that have directly investigated the effects of climate change related stressors. Phenotypic plasticity in response to climate change, specifically ocean warming, may be a species’ best chance of resilience given the expedited rate of environmental change. However, despite extensive research on plasticity within and across generations in teleost fishes, there remains a knowledge gap for elasmobranch species, owing to their extended life spans and delayed sexual maturity. Here, we present four case studies on different elasmobranch species to lend perspectives on the capacity for phenotypic plasticity within the context of ocean warming. Furthermore, we discuss potential research avenues and modern technologies that may enable future investigations to empirically explore the capacity for phenotypic plasticity in elasmobranchs.